Pemberian Layanan Tes Bakat dan Minat Karier (Analisis Artistik dan Sosial) - Wirastania, Aniek; Lianawati, Ayong; Hartanti, Jahju; Sutijono Sutijono; Munawaroh, Allisa Qotrunnada (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Aptitude test and career interest is one of the efforts carried out in the form of a series of tests and analysis in describing the cognitive abilities, character, talents, interests and personality of an individual in order to determine a particular major. This interest aptitude test is very helpful and has a significant influence on the success of an individual in determining and planning a future career. The problem faced by students today is the difficulty in directing their talents and career interests according to their abilities. Efforts to overcome the problems faced by individuals must be carried out effectively. The activity carried out is to carry out tests of student aptitude and career interest. This aptitude and career interest test was conducted on class XII students of Integrated Bilingual Middle School, Krian District, Sidoarjo Regency. The method of carrying out the activity of providing aptitude and career interest test services is carried out with the following stages, namely administration, analysis of the number of students taking the aptitude test and student career interest, administering the test, directing the results of the aptitude test and student career interest, as well as evaluating the implementation of the aptitude and interest test student career. Providing student aptitude and career interest test services can assist students in planning further studies at the next level of education according to their talents and interests.